Characteristic changes in microbial community composition and expression of innate immune genes in acute appendicitis. Issue 1 (January 2015) - Arlt, Alexander; Bharti, Richa; Ilves, Imre; Häsler, Robert; Miettinen, Pekka; Paajanen, Hannu; Brunke, Gabriele; Ellrichmann, Mark; Rehman, Ateequr; Hauser, Charlotte; Egberts, Jan-Hendrik; Ott, Stephan J; et al.
Appendicitis represents a common and severe gastrointestinal illness in younger individuals worldwide. The disease is characterized by an excessive inflammatory response and it is believed that bacterial overgrowth due to blockage of the appendix lumen might be involved. Despite the high incidence, only limited data on the pathophysiological changes exist; in particular, the innate immune responses involved are largely unknown. Real-time PCR analysis of tissue samples from inflamed and normal appendices demonstrated differentially regulated expression patterns of epithelial-derived antimicrobial peptides (AMP). The α-defensins human neutrophil peptides 1–3, HD5 and HD6, as well as the two β-defensins, human β-defensins (hBD)-2 and hBD-3, were up-regulated, whereas hBD-1 was down-regulated in acute appendicitis. Expression of upstream regulators of AMP expression, NOD-2 and TLRs 1, 2, 4, 5, 7, 8 and 10 was significantly increased as detected by real-time PCR. Finally, we confirmed the involvement of the pro-inflammatory cytokines IL-1β and IL-8, and detected characteristic changes in microbial community composition in appendicitis tissue specimens by 16S rDNA based detection techniques. In this study, we demonstrate a differential regulation of the innate immune system along with an altered bacterial diversity in acute appendicitis.